Formulation and Development of Spirulina (Athrospira plantasis) Loaded Chocolatesas Immunity Boosters - Shweta Prashant Ghode; Prashant D Ghode; Vibhavari M Chatur; Rohini Kolhe; Sandesh Patil (International Journal of Phytomedicine, 2020)
Adults, as well as children, have a great need for nutrients such as Calcium, Iron, Zinc, Protein, and Vitamin B12. Spirulina is very rich in protein, omega 3 and omega 6 oils, vitamin, and mineral, and its incorporation into chocolates will enrich their nutritional values. Spirulina satisfies the nutritional needs by providing all these nutrients, as well as all the essential amino acids. Spirulina is unique and 100% safe. In fact, Spirulina is the only natural food that contains GLA (gamma linoleic acid) an essential fatty acid that is found only in mother’s milk. This GLA plays a very vital in balancing the hormonal system in the body. So it is actually very good to give Spirulina to the children. Our Spirulina Chocolates were prepared by simple incorporation method by addition of 1gm Spirulina by dissolving in 10 ml NaCl as a solubility enhancer as well as to mask the taste and smell. This chocolate form is easier for every individual to chew and absorb. The chocolates were assessed for organoleptic properties, pH, blooming test, and hardness. This significant study revealed the efficacy of Spirulina Chocolate Formulation and it would definitely have a wide scope in the future as an immunity booster and in treatments of malnutrition in children as well. Further study is required to reveal the quantification of constituents present in Spirulina Chocolate formulation by in vivo and invitro studies.